2008
DOI: 10.1359/jbmr.080511
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-Induced Osteopetrosis: Novel Bone Modeling Defects, Metaphyseal Osteopenia, and Osteosclerosis Fractures After Drug Exposure Ceases

Abstract: ABSTRACT:In 2003, we reported on a 12-yr-old boy who had developed osteopetrosis (OPT) while receiving pamidronate (PMD) for idiopathic bone pain and enigmatic elevation in circulating bone alkaline phosphatase. Now 17 yr of age, he was re-evaluated 6.5 yr after PMD exposure stopped. Our patient described less bone pain but further limb fractures. His growth plates were fused, yet hyperphosphatasemia persisted. Radiographs documented interval fractures of a metacarpal, an osteosclerotic distal radius, and a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 46 publications
3
57
0
Order By: Relevance
“…In 2 unrelated children referred with pamidronate-induced OPT (Fig. 5C, D), serum LDH and AST were not elevated (8,18) (data not shown). Two unrelated infants at St Louis Children's Hospital with severe autosomal recessive (''malignant'') OPT due to compound heterozygous TGIRG1 mutations had serum LDH levels that were elevated at 677 and 1235 U/L (normal 130 to 400 U/L for ages 1 month to 5 years); however, LDH isoenzyme quantitation was not performed because myelophthisic marrow AE2 SD mean from 5 pediatric patients with nonosteosclerotic bone disorders and normal serum total LDH and AST levels.…”
Section: Osteopetrosis (Ldh and Ast Values)mentioning
confidence: 79%
See 2 more Smart Citations
“…In 2 unrelated children referred with pamidronate-induced OPT (Fig. 5C, D), serum LDH and AST were not elevated (8,18) (data not shown). Two unrelated infants at St Louis Children's Hospital with severe autosomal recessive (''malignant'') OPT due to compound heterozygous TGIRG1 mutations had serum LDH levels that were elevated at 677 and 1235 U/L (normal 130 to 400 U/L for ages 1 month to 5 years); however, LDH isoenzyme quantitation was not performed because myelophthisic marrow AE2 SD mean from 5 pediatric patients with nonosteosclerotic bone disorders and normal serum total LDH and AST levels.…”
Section: Osteopetrosis (Ldh and Ast Values)mentioning
confidence: 79%
“…Indeed, our reported patient referred with pamidronate (PMD)-induced OPT (8) had increases in serum TRACP-5b and BB-CK 1½ years after PMD exposure stopped (8) but not 6 years later when his osteoclasts resumed functioning. (18) His serum LDH and AST levels were normal at both time points. (8,18) On referral, our second (unpublished) patient with PMD-induced OPT (Fig.…”
Section: Ldh Elevation In A-sdmentioning
confidence: 91%
See 1 more Smart Citation
“…The regimens have varied based mainly on the ease of administration, convenience and age of the patient. Complications of bisphosphonate therapy are well reported in adults and children mainly for the treatment of malignancy and malignant hypercalcaemia, where high doses of up to 3 mg/kg/day are used [19][20][21]. These include fever, symptomatic hypocalcaemia, renal and ophthalmic toxicity [8,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…(10) Atypical subtrochanteric femoral fractures, as seen in our patient, have been described previously in pycnodysostosis, (11)(12)(13) osteopetrosis, (14,15) and hypophosphatasia, (16,17) but recent case series demonstrate a potential association between similar fractures and bisphosphonate use. (18)(19)(20) A review of over 14,000 women from bisphosphonate trials, however, found the occurrence of these fractures to be rare. (21) It is possible that there is a genetic predisposition to atypical subtrochanteric fractures, and polymorphisms of the gene encoding cathepsin K could be such a candidate gene.…”
Section: Discussionmentioning
confidence: 99%